Burnout syndrome: are stroke neurologists at a higher risk? - Viviane Flumignan Zétola; Giovana Memari Pavanelli; Gabriella Ueharo Pereira; Francisco Manoel Branco Germiniani; Marcos Christiano Lange (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Burnout syndrome is a work-related psychological response, characterized by emotional exhaustion, depersonalization and low professional accomplishment. Objective: The study aimed to evaluate the prevalence of burnout syndrome in neurologists in the State of Paraná, Brazil, dividing them into stroke neurologists and non-stroke neurologists. Methods: We performed a crosssectional observational study, with a quantitative approach, based on the online Maslach Burnout Inventory - Human Services Survey questionnaire. Results: A total of 74 neurologists were evaluated, 44.6% of whom had burnout syndrome, predominantly among females and stroke neurologists. Both the stroke neurologist and non-stroke neurologist groups had medium degrees of emotional exhaustion and depersonalization; however, while stroke neurologists had high professional accomplishment, non-stroke neurologists had mean-to-low scores of professional accomplishment. There was a proportional relationship between age and emotional exhaustion. Female neurologists also reported lower professional accomplishment levels. Conclusion: Burnout is prevalent among the neurologists of Paraná, corroborating the results previously reported in other studies. There seems to be no significant difference between those neurologists who work in the emergency stroke care setting compared with those who don't.